Lipidic cubic phase serial millisecond crystallography using synchrotron radiation. (2015) - Nogly, Przemyslaw; James, Daniel; Wang, Dingjie; White, Thomas A.; Zatsepin, Nadia; Shilova, Anastasya
No abstract available